Views of the public about Snacktivity™: a small changes approach to promoting physical activity and reducing sedentary behaviour - K. Gokal; R. Amos-Hirst; C. A. Moakes; J. P. Sanders; D. W. Esliger; L. B. Sherar; N. Ives; S. J. H. Biddle; C. Edwardson; T. Yates; E. Frew; C. Greaves; et al. (BMC, 2022)
Abstract Background Many people do not meet the recommended health guidance of participation in a minimum of 150-300 min of moderate intensity physical activity per week, often promoted as at least 30 min of physical activity on 5 days of the week. This is concerning and highlights the importance of finding innovative ways to help people to be physically active each day. Snacktivity™ is a novel approach that aims to encourage people to do small, 2-5 min bouts of physical activity 'snacks' throughout the whole day, such that they achieve at least 150 min of moderate intensity activity per week. However, before it can be recommended, there is a need to explore whether the concept is acceptable to the public. Methods A survey to assess the views of the public about Snacktivity™ was distributed to adult patients registered at six general practices in the West Midlands, UK and to health care employees in the same region. Results A total of 5989 surveys were sent to patients, of which 558 were returned (9.3%). A further 166 surveys were completed by health care employees. A total of 85% of respondents liked the Snacktivity™ concept. The flexibility of the approach was highly rated. A high proportion of participants (61%) reported that the ability to self-monitor their behaviour would help them to do Snacktivity™ throughout their day. Physically inactive participants perceived that Snacktivity™ would help to increase their physical activity, more than those who were physically active (OR = 0.41, 95% CI: 0.25-0.67). Approximately 90% of respondents perceived that Snacktivity™ was easy to do on a non-working day compared to 60% on a working day. Aerobic activity 'snacks' were preferred to those which were strength based. Conclusions The Snacktivity™ approach to promoting physical activity was viewed positively by the public and interventions to test the merits of such an approach now need to be developed and tested in a variety of everyday contexts.